Socialisation of Adolescents with Cognitive Disorders through Emotional Intelligence - Vovchenko, Olha A.; Lytvynova, Nataliia A.; Tsekhmister, Yaroslav V.; Hoshovska, Dariia T.; Vichalkovska, Natalia K. (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Objective: To study the influence of the development of emotional intelligence of adolescents with CDs through the involvement of their parents and teachers in socialisation. The emotional sphere of adolescents with cognitive disorders (CDs) is no less important than correcting their cognitive development. The methods that allow fixing the patients’ ability to recognise emotions don’t realise the functioning of their emotional sphere. Method: Questionnaires were used for diagnosing the emotional interaction of parents and teachers with adolescents with CD, the questionnaire for measuring the socialisation of adolescents "How adapted I am to life" by A. Furman, statistical analysis ANOVA, correlation analysis r of Pearson, content analysis of the qualitative data. Results: Standardised questionaries developed that reflect the formation of emotional intelligence of the adolescent with CDs through the interaction with their parents and teachers. Empirical data obtained while research resulted in statistically significant correlations of emotional intelligence between parents, teachers and psychologists and social adaptation measured via Furman questionary. It was found that the positive emotional interaction and tactile support of adolescents with CDs with their parents increases the level of social adaptation. Similar correlations were found in teachers’ emotional interaction with the adolescents with CDs. The number of parents who showed a low emotional and tactile interaction with adolescents was 20%. Conclusions: Detected statistically significant correlations proved that the high role of the participation of parents and teachers in the process of forming emotional intelligence contributes to the successful socialisation of adolescents with cognitive disorders.